Use of Poisonous Plants in Traditional Antidotes of Snake Poison in Sagar Region of Central India - Choubey, V. B.; Khare, P. K. (Indian Forester, 2013)
The rural population use poisonous plants as an antidote of snake poison since long time. A preliminarily survey was conducted for poisonous plants used in snake bite problem in tropical dry deciduous forests of Sagar region and its environs in Central India. The paper includes a list of wild and cultivated poisonous plants common to this region which are hitherto not systematically reported. A total number of 15 species belonging to 13 families and 12 genera were collected. Out of these, eight herbs, one shrub and six tree species were classified. These plants are used traditionally as an indigenous medicine in snake bite problem, but these plants are harmful for humans and livestocks. Plant habit, chemical constituents, toxic part and use of snake antidotes have been described and discussed.